Boron nitride particles, method for producing boron nitride particles, resin composition, and method for producing resin composition
By producing boron nitride particles with large sizes and aspect ratios through a novel method, thermal conductivity is enhanced, addressing limitations of conventional methods and improving heat dissipation materials.
Patent Information
- Application Number
- JP2022544001
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-08-20
- Filing Date
- 2021-08-19
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2041-08-19
AI Technical Summary
Conventional methods for producing boron nitride particles are limited in size and aspect ratio, hindering the enhancement of thermal conductivity when used as heat dissipating materials.
A method involving a mixture of boron carbide and boric acid in a carbon container under a nitrogen atmosphere, with heating and pressurization to produce boron nitride particles with maximum lengths of 80 μm or more and aspect ratios of 1.5 or more, which can be mixed with resin to form a resin composition.
The resulting boron nitride particles enhance thermal conductivity by reducing heat transfer loss and weight, making them suitable for heat dissipation materials with improved performance.
Smart Images

Figure 0007626356000001 
Figure 0007626356000002 
Figure 0007626356000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to boron nitride particles, a method for producing boron nitride particles, a resin composition, and a method for producing a resin composition. [Background technology]
[0002] Boron nitride has lubricating properties, high thermal conductivity, and insulating properties, and is used in a variety of applications, such as as a solid lubricant, a release material, a cosmetic ingredient, a heat dissipation material, and a sintered body having heat resistance and insulating properties.
[0003] For example, Patent Document 1 describes a hexagonal boron nitride powder that can impart high thermal conductivity and high dielectric strength to a resin composition obtained by filling the resin with the powder, which contains aggregated particles made of primary particles of hexagonal boron nitride and has a BET specific surface area of 0.7 to 1.3 m. 2 / g and an oil absorption measured in accordance with JIS K 5101-13-1 of 80 g / 100 g or less is disclosed. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2016-160134 A Summary of the Invention [Problem to be solved by the invention]
[0005] As disclosed in the above Patent Document 1, when boron nitride particles are used as a heat dissipation material, for example, it is desirable to make the boron nitride particles as large as possible in order to increase thermal conductivity. Also, when it is desired to increase thermal conductivity in a specific direction, it is desirable to increase the aspect ratio of the boron nitride particles. However, there is a limit to the size and aspect ratio of boron nitride particles obtained by conventional manufacturing methods.
[0006] A primary object of the present invention is to provide novel boron nitride particles and a method for producing the same. [Means for solving the problem]
[0007] One aspect of the present invention is a method for producing boron nitride particles, comprising the steps of placing a mixture containing boron carbide and boric acid, and a substrate formed of a carbon material, in a container formed of a carbon material, and generating boron nitride particles on the substrate by heating and pressurizing the container in a nitrogen atmosphere.
[0008] The pressure may be 0.3 MPa or more.
[0009] According to the above-mentioned production method, it is possible to obtain boron nitride particles having a size and aspect ratio that could not be obtained by conventional production methods. That is, another aspect of the present invention is boron nitride particles having a maximum length of 80 μm or more and an aspect ratio of 1.5 or more.
[0010] The maximum length may be 150 μm or more.
[0011] The boron nitride particles may have an outer shell formed of boron nitride and a hollow portion surrounded by the outer shell.
[0012] Another aspect of the present invention is a resin composition containing the above boron nitride particles and a resin.
[0013] Another aspect of the present invention is a method for producing a resin composition comprising the steps of preparing the boron nitride particles and mixing the boron nitride particles with a resin. The method for producing a resin composition may further comprise the step of pulverizing the boron nitride particles. Effect of the Invention
[0014] According to one aspect of the present invention, it is possible to provide novel boron nitride particles and a method for producing the same. [Brief description of the drawings]
[0015] [Figure 1] FIG. 2 is a schematic diagram showing one embodiment of pulverized boron nitride particles (pulverized boron nitride particles). [Diagram 2] 1 is a graph showing the results of X-ray diffraction measurement of the boron nitride particles of Example 1. [Diagram 3] 1 is a SEM image of boron nitride particles of Example 1. [Figure 4] 1 is a SEM image of boron nitride particles of Example 2. [Diagram 5] 1 is a SEM image of boron nitride particles of Example 3. [Figure 6] 1 is a SEM image of boron nitride particles of Example 4. [Figure 7] 1 is a SEM image of boron nitride particles of Example 5. [Figure 8] 1 is an SEM image of the boron nitride particles of Example 1 after grinding. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS An embodiment of the present invention is a boron nitride particle having a maximum length of 80 μm or more and an aspect ratio of 1.5 or more.
[0017] The boron nitride particles according to one embodiment have excellent thermal conductivity (particularly thermal conductivity in the longitudinal direction of the boron nitride particles) due to the large maximum length and aspect ratio. Therefore, the boron nitride particles can be suitably used as a heat dissipation material (heat dissipation sheet). Although a heat dissipation material has been exemplified as an application of the boron nitride particles, the boron nitride particles can be used for various applications other than the heat dissipation material.
[0018] In one embodiment, the boron nitride particle may be composed of a plurality of boron nitride pieces. The boron nitride pieces are formed of boron nitride and may have, for example, a scale-like shape. In this case, the length of the boron nitride pieces in the longitudinal direction may be, for example, 1 μm or more and 10 μm or less. The plurality of boron nitride pieces constituting the boron nitride particle may be in physical contact with each other or may be chemically bonded.
[0019] The maximum length of the boron nitride particles may be 100 μm or more, 125 μm or more, 150 μm or more, 175 μm or more, 200 μm or more, 225 μm or more, 250 μm or more, 300 μm or more, or 350 μm or more, and may be 500 μm or less.
[0020] The maximum length of a boron nitride particle means the maximum linear distance between any two points on a single boron nitride particle when the particle is observed under a scanning electron microscope (SEM). The maximum length may be measured by importing the SEM image into image analysis software (for example, "Mac-view" manufactured by Mountec Co., Ltd.).
[0021] Because the boron nitride particles have a large maximum length, for example, when the boron nitride particles are mixed with a resin to form a heat dissipation material, the number of boron nitride particles aligned in the thickness direction of the heat dissipation material is reduced, and heat transfer loss between the boron nitride particles is reduced, which is thought to result in the heat dissipation material having better thermal conductivity.
[0022] The aspect ratio of the boron nitride particles may be 1.7 or more, 2.0 or more, 3.0 or more, 5.0 or more, or 7.0 or more, and may be 12.0 or less, 10.0 or less, 9.5 or less, 9.0 or less, or 8.0 or less.
[0023] The aspect ratio of a boron nitride particle is the maximum length (maximum length in the longitudinal direction) L A and the maximum length L A The maximum length of the boron nitride particle in the direction perpendicular to the direction of the length (longitudinal direction) (maximum length in the transverse direction) L BRatio to (L A / L B ) is defined as the maximum length L B is the maximum length in the longitudinal direction L A It can be measured in the same manner as above.
[0024] The larger the aspect ratio of the boron nitride particles, the more elongated the boron nitride particles are. Therefore, for example, when the boron nitride particles are mixed with a resin to form a heat dissipating material, the boron nitride particles tend to overlap each other. Furthermore, when the boron nitride particles overlap with other boron nitride particles, the elongated boron nitride particles are thought to overlap at an angle. Therefore, the number of boron nitride particles aligned in the thickness direction of the heat dissipating material is reduced, and the heat transfer loss between the boron nitride particles is reduced, so that the heat dissipating material has better thermal conductivity.
[0025] The boron nitride particles may be solid or hollow. When the boron nitride particles are hollow, the boron nitride particles may have an outer shell formed by boron nitride and a hollow portion surrounded by the outer shell. The hollow portion may be formed along the longitudinal direction of the boron nitride particles, and may have an elongated shape that is approximately similar to the external shape of the boron nitride particles. When the boron nitride particles are hollow, at least one of both ends in the longitudinal direction of the boron nitride particles may be an open end, and both ends may be open ends. The open end may be connected to the hollow portion described above. When the boron nitride particles are hollow and at least one of both ends in the direction of the maximum length of the boron nitride particles is an open end, for example, when the boron nitride particles are mixed with a resin and used as a heat dissipating material, the hollow portion is filled with a resin that is lighter than the boron nitride particles, and the heat dissipating material can be expected to have an improved thermal conductivity and a lighter weight.
[0026] The boron nitride particles may have a cross section in which the area ratio of the hollow portion to the total area of the shell portion and the hollow portion is 5% or more. The area ratio of the hollow portion of the boron nitride particles can be determined by importing a cross-sectional image (SEM image) of the boron nitride particles into image analysis software (for example, "Mac-view" manufactured by Mountec Co., Ltd.) and calculating. From the viewpoint of reducing the weight of a heat dissipation material when used in the heat dissipation material, the boron nitride particles may have a cross section in which the above-mentioned area ratio is 10% or more, 20% or more, 30% or more, 40% or more, or 50% or more, and may have a cross section in which the above-mentioned area ratio is 90% or less or 80% or less.
[0027] The thickness of the outer shell may be 50 μm or less, and from the viewpoint of further reducing the weight of the boron nitride particles, it is preferably 30 μm or less, and more preferably 15 μm or less. From the viewpoint of easily maintaining the shape of the boron nitride particles, the thickness of the outer shell may be 1 μm or more or 3 μm or more. The thickness of the outer shell is defined as the average length of the line drawn on each outer shell when a line that maximizes the straight line distance between any two points is drawn on the cross section of the boron nitride particle in an observation image obtained by observing the cross section of the boron nitride particle in a direction perpendicular to the longitudinal direction with an SEM.
[0028] The boron nitride particles may be either definite or irregular in shape. The external shape of the boron nitride particles may be spheroidal, columnar (rod-like), plate-like (flat, curved, etc.), dumbbell-like, etc. The boron nitride particles may have a branched structure that branches in two or more directions.
[0029] The boron nitride particles may consist essentially of boron nitride. Whether the boron nitride particles consist essentially of boron nitride can be confirmed by detecting only peaks derived from boron nitride in an X-ray diffraction measurement.
[0030] Next, the above-mentioned method for producing boron nitride particles will be described below. The boron nitride particles can be produced by a method for producing boron nitride particles, comprising the steps of: arranging a mixture containing boron carbide and boric acid and a substrate made of a carbon material in a container made of a carbon material (arrangement step); and heating and pressurizing the container in a nitrogen atmosphere to produce boron nitride particles on the substrate (production step). Another embodiment of the present invention is such a method for producing boron nitride particles.
[0031] The container made of a carbon material is a container capable of containing the mixture and the base material. The container may be, for example, a carbon crucible. The container is preferably a container whose airtightness can be enhanced by covering the opening. In the arrangement step, for example, the mixture may be arranged at the bottom of the container, and the base material may be arranged so as to be fixed to the side wall surface or the inside of the lid of the container. The base material made of a carbon material may be, for example, a sheet, plate, or rod. The base material made of a carbon material may be, for example, a carbon sheet (graphite sheet), a carbon plate, or a carbon rod.
[0032] The boron carbide in the mixture may be, for example, in powder form (boron carbide powder). The boric acid in the mixture may be, for example, in powder form (boric acid powder). The mixture may be obtained, for example, by mixing boron carbide powder and boric acid powder by a known method.
[0033] The boron carbide powder can be produced by a known production method. For example, the method for producing the boron carbide powder includes mixing boric acid with acetylene black, and then heating the mixture at 1800 to 2400°C for 1 to 10 hours in an inert gas (e.g., nitrogen gas) atmosphere to obtain aggregated boron carbide particles. The aggregated boron carbide particles obtained by this method can be crushed, sieved, washed, impurity removed, dried, etc., to obtain boron carbide powder.
[0034] The average particle size of the boron carbide powder can be adjusted by adjusting the grinding time of the aggregated boron carbon particles. The average particle size of the boron carbide powder may be 5 μm or more, 7 μm or more, or 10 μm or more, and may be 100 μm or less, 90 μm or less, 80 μm or less, or 70 μm or less. The average particle size of the boron carbide powder can be measured by a laser diffraction scattering method.
[0035] The mixing ratio of boron carbide and boric acid can be appropriately selected. The content of boric acid in the mixture is preferably 2 parts by mass or more, more preferably 5 parts by mass or more, and even more preferably 8 parts by mass or more, relative to 100 parts by mass of boron carbide, from the viewpoint that boron nitride particles tend to become large, and may be 100 parts by mass or less, 90 parts by mass or less, or 80 parts by mass or less.
[0036] The mixture containing boron carbide and boric acid may further contain other components, such as silicon carbide, carbon, iron oxide, etc. When the mixture containing boron carbide and boric acid further contains silicon carbide, it becomes easier to obtain boron nitride particles that do not have open ends.
[0037] The inside of the container is a nitrogen atmosphere containing, for example, 95% by volume or more of nitrogen gas. The content of nitrogen gas in the nitrogen atmosphere is preferably 95% by volume or more, more preferably 99.9% by volume or more, and may be substantially 100% by volume. In addition to nitrogen gas, the nitrogen atmosphere may contain ammonia gas, etc.
[0038] From the viewpoint that boron nitride particles tend to grow large, the heating temperature is preferably 1450° C. or higher, more preferably 1600° C. or higher, and even more preferably 1800° C. or higher. The heating temperature may be 2400° C. or lower, 2300° C. or lower, or 2200° C. or lower.
[0039] The pressure during pressing is preferably 0.3 MPa or more, more preferably 0.6 MPa or more, from the viewpoint that boron nitride particles tend to become large. The pressure during pressing may be 1.0 MPa or less, or 0.9 MPa or less.
[0040] The time for which the heating and pressure are applied is preferably 3 hours or more, more preferably 5 hours or more, from the viewpoint that boron nitride particles tend to become large. The time for which the heating and pressure are applied may be 40 hours or less, or 30 hours or less.
[0041] According to this manufacturing method, boron nitride particles having the above-mentioned maximum length are generated on a substrate formed of a carbon material. Therefore, boron nitride particles are obtained by recovering the boron nitride particles on the substrate. The fact that the particles generated on the substrate are boron nitride particles can be confirmed by recovering a portion of the particles from the substrate, performing X-ray diffraction measurement on the recovered particles, and detecting a peak derived from boron nitride.
[0042] The boron nitride particles obtained as described above may be subjected to a classification step (classification step) so as to obtain only boron nitride particles having a maximum length within a specific range among boron nitride particles having a maximum length of 80 μm or more and an aspect ratio of 1.5 or more.
[0043] The boron nitride particles obtained as described above can be mixed with a resin to be used as a resin composition. That is, another embodiment of the present invention is a resin composition containing the above boron nitride particles and a resin.
[0044] Examples of resins include epoxy resin, silicone resin, silicone rubber, acrylic resin, phenolic resin, melamine resin, urea resin, unsaturated polyester, fluororesin, polyimide, polyamideimide, polyetherimide, polybutylene terephthalate, polyethylene terephthalate, polyphenylene ether, polyphenylene sulfide, wholly aromatic polyester, polysulfone, liquid crystal polymer, polyethersulfone, polycarbonate, maleimide-modified resin, ABS (acrylonitrile-butadiene-styrene) resin, AAS (acrylonitrile-acrylic rubber-styrene) resin, and AES (acrylonitrile-ethylene-propylene-diene rubber-styrene) resin.
[0045] When the resin composition is used as a heat dissipation material, the content of the boron nitride particles may be 15% by volume or more, 20% by volume or more, 30% by volume or more, 40% by volume or more, 50% by volume or more, or 60% by volume or more based on the total volume of the resin composition, from the viewpoint of improving the thermal conductivity of the heat dissipation material and easily obtaining excellent heat dissipation performance. The content of the boron nitride particles may be 85% by volume or less, 80% by volume or less, 70% by volume or less, 60% by volume or less, 50% by volume or less, or 40% by volume or less based on the total volume of the resin composition, from the viewpoint of suppressing the generation of voids when the resin composition is molded into a sheet-shaped heat dissipation material and suppressing the deterioration of the insulation and mechanical strength of the sheet-shaped heat dissipation material.
[0046] The resin content may be appropriately adjusted depending on the application, required properties, etc. of the resin composition. The resin content may be, for example, 15 volume% or more, 20 volume% or more, 30 volume% or more, 40 volume% or more, 50 volume% or more, or 60 volume% or more based on the total volume of the resin composition, and may be 85 volume% or less, 70 volume% or less, 60 volume% or less, 50 volume% or less, or 40 volume% or less.
[0047] The resin composition may further contain a curing agent for curing the resin. The curing agent is appropriately selected according to the type of resin. For example, curing agents used together with the epoxy resin include phenol novolac compounds, acid anhydrides, amino compounds, imidazole compounds, etc. The content of the curing agent may be, for example, 0.5 parts by mass or more or 1.0 parts by mass or more, and 15 parts by mass or less or 10 parts by mass or less, relative to 100 parts by mass of the resin.
[0048] The resin composition may further contain other components, such as a curing accelerator (curing catalyst), a coupling agent, a wetting / dispersing agent, a surface conditioner, etc.
[0049] Examples of the curing accelerator (curing catalyst) include phosphorus-based curing accelerators such as tetraphenylphosphonium tetraphenylborate and triphenyl phosphate, imidazole-based curing accelerators such as 2-phenyl-4,5-dihydroxymethylimidazole, and amine-based curing accelerators such as boron trifluoride monoethylamine.
[0050] Examples of the coupling agent include a silane-based coupling agent, a titanate-based coupling agent, and an aluminate-based coupling agent, etc. Examples of the chemical bonding group contained in these coupling agents include a vinyl group, an epoxy group, an amino group, a methacryl group, and a mercapto group.
[0051] Examples of the wetting and dispersing agent include phosphate salts, carboxylate esters, polyesters, acrylic copolymers, and block copolymers.
[0052] Examples of the surface conditioner include an acrylic surface conditioner, a silicone surface conditioner, a vinyl surface conditioner, and a fluorine surface conditioner.
[0053] The resin composition can be produced by a method for producing a resin composition, comprising, for example, a step of preparing boron nitride particles according to one embodiment (preparation step) and a step of mixing the boron nitride particles with a resin (mixing step). Another embodiment of the present invention is a method for producing such a resin composition.
[0054] The method for producing a resin composition according to an embodiment may further include a step of pulverizing the boron nitride particles (pulverizing step). The pulverizing step may be performed between the preparation step and the mixing step, or may be performed simultaneously with the mixing step (the boron nitride particles may be pulverized at the same time as mixing the boron nitride particles with the resin).
[0055] The boron nitride particles pulverized in the pulverization step (hereinafter also referred to as boron nitride pulverized particles) have a bent shape. FIG. 1 is a schematic diagram showing one embodiment of boron nitride pulverized particles. As shown in FIG. 1, in one embodiment, the boron nitride pulverized particles 1 have, for example, a first portion 1a extending in a first direction and a second portion 1b bent from the first portion 1a and extending in a second direction different from the first direction. The fact that the boron nitride pulverized particles have such a bent shape can be confirmed by observing the boron nitride pulverized particles with a scanning electron microscope (SEM). Specifically, as shown in Figure 1, when a straight line L1 is drawn connecting an arbitrary point P1 on one end (the end of the first part 1a) 1c of the boron nitride crushed particle 1 and an arbitrary point P2 on the other end (the end of the second part 1b) 1d in an SEM image of the boron nitride crushed particle 1, if the straight line L1 can be drawn passing through a region R where no boron nitride crushed particle 1 is present, the boron nitride crushed particle 1 is determined to have a bent shape.
[0056] The degree of bending of the boron nitride pulverized particles can be evaluated, for example, by the bending index defined as follows. That is, as shown in FIG. 1, first, in the SEM image of the boron nitride pulverized particles 1, a point P3 is determined at which the length of the perpendicular line drawn from the above-mentioned straight line L1 or its extension to a point on the boron nitride pulverized particles 1 is maximum, and a perpendicular line L2 is drawn from the point P3 to the straight line L1 or its extension. At this time, the bending index is defined as the ratio of the length of the perpendicular line L2 to the length of the straight line L1 (bending index=length of perpendicular line L2 / length of straight line L1). The length of the straight line L1 and the length of the perpendicular line L2 may be measured by importing the SEM image into image analysis software (for example, "Mac-view" manufactured by Mountec Co., Ltd.).
[0057] The larger the bending index, the more the boron nitride pulverized particles are bent (at a sharper angle). The bending index of the boron nitride pulverized particles may be 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, 0.6 or more, 0.7 or more, 0.8 or more, 0.9 or more, 1.0 or more, 1.5 or more, 2.0 or more, or 3.0 or more, and may be 10 or less, 8.0 or less, 6.0 or less, 5.0 or less, or 4.0 or less. Although multiple straight lines L1 can be drawn for one boron nitride pulverized particle, if at least one straight line L1 can be drawn such that the bending index of the boron nitride pulverized particles falls within the above range, the bending index of the boron nitride pulverized particles is considered to be in the above range. The same applies to the numerical range related to the straight line L1 below.
[0058] The length of the straight line L1 may be 10 μm or more, 20 μm or more, 30 μm or more, 40 μm or more, or 50 μm or more, and may be 150 μm or less or 100 μm or less. The length of the perpendicular line L2 may be 10 μm or more, 20 μm or more, 30 μm or more, 40 μm or more, or 50 μm or more, and may be 150 μm or less or 100 μm or less.
[0059] The angle between the first portion 1a (first direction) and the second portion 1b (second direction) may be 20 to 150°. The angle may be 30° or more, 40° or more, 50° or more, or 60° or more, and may be 140° or less, 120° or less, or 100° or less.
[0060] The angle between the first portion 1a (first direction) and the second portion 1b (second direction) is defined as follows. That is, as shown in Fig. 1, point P3 and point P1 on one end (end of the first portion 1a) 1c of the boron nitride pulverized particle 1 are connected by a straight line L3, and point P3 and point P2 on the other end (end of the second portion 1b) 1d are connected by a straight line L4. At this time, the angle φ between the straight lines L3 and L4 is defined as the angle between the first portion 1a (first direction) and the second portion 1b (second direction).
[0061] The length of the first portion 1a and the second portion 1b may each independently be 10 μm or more, 20 μm or more, 30 μm or more, 40 μm or more, or 50 μm or more, and may be 150 μm or less, or 100 μm or less.
[0062] The length of the first portion 1a is defined as the length of the above-mentioned straight line L3. The length of the second portion is defined as the length of the above-mentioned straight line L4. The lengths of the first portion 1a and the second portion 1b may be measured by importing the SEM image into image analysis software (for example, "Mac-view" manufactured by Mountec Co., Ltd.).
[0063] The aspect ratios of the first portion 1a and the second portion 1b may each independently be 1.1 or more, 1.2 or more, 1.3 or more, 1.4 or more, 1.5 or more, 2.0 or more, or 3.0 or more, and may be 12.0 or less, 10.0 or less, 9.0 or less, 8.0 or less, 7.0 or less, or 6.0 or less.
[0064] The aspect ratio of the first portion is defined as the ratio (L3 / L5) of the length (L3) of the first portion to the maximum length (L5) in a direction perpendicular to the direction of the length. The maximum length (L5) in a direction perpendicular to the direction of the length of the first portion can be measured in the same manner as the length (L3) of the first portion. The aspect ratio of the second portion is defined by replacing the above definition of "first portion" with "second portion."
[0065] The above resin composition can be used as, for example, a heat dissipation material. The heat dissipation material can be produced, for example, by curing the resin composition. The method for curing the resin composition is appropriately selected according to the type of resin (and the curing agent used as necessary) contained in the resin composition. For example, when the resin is an epoxy resin and the above-mentioned curing agent is used together, the resin can be cured by heating, and pressure may be applied together with heating. EXAMPLES
[0066] The present invention will be described in detail below with reference to examples, although the present invention is not limited to the following examples.
[0067] Example 1 The boron carbide particles in the form of clumps were pulverized by a pulverizer to obtain boron carbide powder with an average particle size of 10 μm. 100 parts by mass of the obtained boron carbide powder and 9 parts by mass of boric acid were mixed and filled into a carbon crucible, the opening of the carbon crucible was covered with a carbon sheet (manufactured by NeoGraf), and the carbon sheet was sandwiched between the carbon crucible lid and the carbon crucible to fix the carbon sheet. The carbon crucible with the lid was heated in a resistance heating furnace under a nitrogen gas atmosphere at 2000° C. and 0.85 MPa for 20 hours to generate particles on the carbon sheet.
[0068] A portion of the particles formed on the carbon sheet was collected and subjected to X-ray diffraction measurement using an X-ray diffractometer (Rigaku Corporation, "ULTIMA-IV"). The results of this X-ray diffraction measurement and the results of X-ray diffraction measurement of boron nitride powder (GP grade) manufactured by Denka Co., Ltd. for comparison are shown in Figure 2. As can be seen from Figure 2, only peaks derived from boron nitride were detected, confirming that boron nitride particles were formed. In addition, an SEM image of the obtained boron nitride particles is shown in Figure 3. One of the obtained boron nitride particles (the boron nitride particle indicated by the arrow in Figure 3) had a columnar shape. The maximum length of the boron nitride particle was 373 μm, and the aspect ratio was 7.5.
[0069] Example 2 Particles were generated on a carbon sheet under the same conditions as in Example 1, except that the content of boron carbide powder and boric acid in the mixture was changed to 97 parts by mass of boron carbide powder and 12 parts by mass of boric acid (12.4 parts by mass of boron carbide powder and 100 parts by mass of boron carbide powder). A part of the particles generated on the carbon sheet was collected and subjected to X-ray diffraction measurement, and only a peak derived from boron nitride was detected, confirming that boron nitride particles were generated. An SEM image of the obtained boron nitride particles is shown in FIG. 4. One of the obtained boron nitride particles (the boron nitride particle indicated by the arrow in FIG. 4) had a branched structure branched in two directions. The maximum length of the boron nitride particle was 365 μm, and the aspect ratio was 8.9.
[0070] Example 3 Particles were generated on a carbon sheet under the same conditions as in Example 1, except that the content of boron carbide powder and boric acid in the mixture was changed to 20 parts by mass of boron acid per 100 parts by mass of boron carbide powder. A part of the particles generated on the carbon sheet was collected and subjected to X-ray diffraction measurement, and only a peak derived from boron nitride was detected, confirming that boron nitride particles were generated. An SEM image of the obtained boron nitride particles is shown in FIG. 5. One of the obtained boron nitride particles (the boron nitride particle indicated by the arrow in FIG. 5) had a branched structure branched in three directions. The maximum length of the boron nitride particle was 206 μm, and the aspect ratio was 1.6.
[0071] Example 4 The surface of the carbon sheet was polished with #80 abrasive paper, and the arithmetic mean roughness of the polished carbon sheet surface in the range of 800 μm × 800 μm was measured using a laser microscope (Optelics HYBRID, manufactured by Lasertec Corporation), and the arithmetic mean roughness was 25 μm. Particles were generated on the carbon sheet under the same conditions as in Example 1, except that this polished carbon sheet was used. A part of the particles generated on the carbon sheet was collected and subjected to X-ray diffraction measurement, and only a peak derived from boron nitride was detected, confirming that boron nitride particles were generated. An SEM image of the obtained boron nitride particles is shown in FIG. 6. One of the obtained boron nitride particles (the boron nitride particle indicated by the arrow in FIG. 6) had a dumbbell-like shape. The maximum length of the boron nitride particle was 413 μm, and the aspect ratio was 3.3.
[0072] Example 5 Particles were generated on the carbon sheet under the same conditions as in Example 1, except that the carbon sheet was dried in a dryer at 200°C for 1 hour before use. A part of the particles generated on the carbon sheet was collected and subjected to X-ray diffraction measurement, and only a peak derived from boron nitride was detected, confirming that boron nitride particles were generated. An SEM image of the obtained boron nitride particles is shown in Figure 7. One of the obtained boron nitride particles (the boron nitride particle indicated by the arrow in Figure 7) had a hollow shape. The maximum length of the boron nitride particle was 186 μm, the aspect ratio was 2.6, and the thickness of the outer shell was 3.2 μm. In addition, the boron nitride particle had a cross section in which the area ratio of the hollow portion was 53%.
[0073] Example 6 1 g of the boron nitride particles obtained in Example 1 was placed in an alumina mortar and crushed for 1 minute using an alumina pestle. An SEM image of the crushed boron nitride particles is shown in FIG. 8. One of the crushed boron nitride particles (boron nitride particle indicated by an arrow in FIG. 8) had a bent shape. Next, 100 parts by mass of naphthalene-type epoxy resin (manufactured by DIC Corporation, HP4032) and 10 parts by mass of an imidazole compound (manufactured by Shikoku Kasei Corporation, 2E4MZ-CN) as a curing agent were mixed, and then 30 parts by mass of the crushed boron nitride particles were further mixed to obtain a resin composition. This resin composition was degassed under reduced pressure of 500 Pa for 10 minutes and applied to a PET sheet to a thickness of 1.0 mm. Then, the mixture was mixed at a temperature of 150° C. and a pressure of 160 kg / cm. 2 When the mixture was heated and pressed for 60 minutes under the above conditions, a sheet having a thickness of 0.5 mm was obtained.
Claims
1. A boron nitride particle comprising a plurality of boron nitride pieces, A boron nitride particle having a maximum length of 175 μm or more, an aspect ratio of 1.5 to 9.0, and being hollow.
2. 2. The boron nitride particle according to claim 1, having an outer shell formed of boron nitride and a hollow portion surrounded by the outer shell.
3. A resin composition comprising the boron nitride particles according to claim 1 or 2 and a resin.
4. A step of preparing the boron nitride particles according to claim 1 or 2; and mixing the boron nitride particles with a resin.
5. The method for producing a resin composition according to claim 4 , further comprising a step of pulverizing the boron nitride particles.
Citation Information
Patent Citations
Hexagonal boron nitride powder and method for producing the same
JP2016160134A
Method for preparing hexagonal boron nitride by templating
US20190276310A1